Biocomputing 2013 2012
DOI: 10.1142/9789814447973_0042
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Protein Catalytic Sites in the Biomedical Literature

Abstract: This paper explores the application of text mining to the problem of detecting protein functional sites in the biomedical literature, and specifically considers the task of identifying catalytic sites in that literature. We provide strong evidence for the need for text mining techniques that address residue-level protein function annotation through an analysis of two corpora in terms of their coverage of curated data sources. We also explore the viability of building a text-based classifier for identifying pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…We have shown that processing full-text papers is important; this is also in agreement with prior work, e.g. the analysis of protein residues in [26], as well as the general observation of differences between abstracts and full texts, with full texts argued to have more ‘content’ [33, 34]. Importantly, our results provide a novel result, quantifying the significant role that processing of additional material linked to the article with text mining plays in increasing the coverage of extracted mutations.…”
Section: Discussionsupporting
confidence: 90%
“…We have shown that processing full-text papers is important; this is also in agreement with prior work, e.g. the analysis of protein residues in [26], as well as the general observation of differences between abstracts and full texts, with full texts argued to have more ‘content’ [33, 34]. Importantly, our results provide a novel result, quantifying the significant role that processing of additional material linked to the article with text mining plays in increasing the coverage of extracted mutations.…”
Section: Discussionsupporting
confidence: 90%
“…The Mutator tool (7) uses regular expressions to recognize mutations and was tested on mutations related to Fabry disease. The LEAP-FS system aims to recognize all protein amino acid mentions in text, including mutations but also bare mentions (29), and subsequent work with that tool addresses identifying relations between residues and their associated proteins in text (30) as well as functional classification of those residues as catalytic (31). …”
Section: Discussionmentioning
confidence: 99%
“…Although we did not attempt to establish the specific nature of the relationship between the SNP and the gene as mentioned in the article, prior work has found that simple co-occurrence of such concepts can be useful to establish a biological relationship (Gabow et al, 2008; Verspoor et al, 2013; Sokolov et al, 2013). …”
Section: Methodsmentioning
confidence: 99%